Ion channel function in translational bovine gallbladder cholangiocyte organoids: establishment and characterization of a novel model system - Nagao, Itsuma; Ambrosini, Yoko M. (Frontiers in Veterinary Science, 2023)
The study of biliary physiology and pathophysiology has long been hindered by the lack of in vitro models that accurately reflect the complex functions of the biliary system. Recent advancements in 3D organoid technology may offer a promising solution to this issue. Bovine gallbladder models have recently gained attention in the investigation of human diseases due to their remarkable similarities in physiology and pathophysiology with the human gallbladder. In this study, we have successfully established and characterized bovine gallbladder cholangiocyte organoids (GCOs) that retain key characteristics of the gallbladder in vivo, including stem cell properties and proliferative capacity. Notably, our findings demonstrate that these organoids exhibit specific and functional CFTR activity. We believe that these bovine GCOs represent a valuable tool for studying the physiology and pathophysiology of the gallbladder with human significance.